Depletion of Microglia in an Ex Vivo Brain Slice Culture Model of West Nile Virus Infection Leads to Increased Viral Titers and Cell Death - Sarah Stonedahl; Jennifer Smith Leser; Penny Clarke; Kenneth L. Tyler (Microbiology Spectrum, 2022)
ABSTRACT West Nile virus (WNV) is a major cause of viral encephalitis in the United States. WNV infection of the brain leads to neuroinflammation characterized by activation of microglia, the resident phagocytic cells of the central nervous system (CNS). In this study, depletion of CNS microglia using the CSF1R antagonist PLX5622 increased the viral load in the brain and decreased the survival of mice infected with WNV (strain TX02). PLX5622 was also used in ex vivo brain slice cultures (BSCs) to investigate the role of intrinsic neuroinflammatory responses during WNV infection. PLX5622 effectively depleted microglia (>90% depletion) from BSCs resulting in increased viral titers (3 to 4-fold increase in PLX5622-treated samples) and enhanced virus-induced caspase 3 activity and cell death. Microglia depletion did not result in widespread alterations in cytokine and chemokine production in either uninfected or WNV infected BSCs. The results of this study demonstrated how microglia contribute to limiting viral growth and preventing cell death in WNV infected BSCs but were not required for the cytokine/chemokine response to WNV infection. This study highlighted the importance of microglia in the protection from neuroinvasive WNV infection and demonstrated that microglia responses were independent of WNV-induced peripheral immune responses. IMPORTANCE WNV infections of the CNS are rare but can have devastating long-term effects. There are currently no vaccines or specific antiviral treatments, so a better understanding of the pathogenesis and immune response to this virus is crucial. Previous studies have shown microglia to be important for protection from WNV, but more work is needed to fully comprehend the impact these cells have on neuroinvasive WNV infections. This study used PLX5622 to eliminate microglia in an ex vivo brain slice culture (BSC) model to investigate the role of microglia during a WNV infection. The use of BSCs provided a system in which immune responses innate to the CNS could be studied without interference from peripheral immunity. This study will allow for a better understanding of the complex nature of microglia during viral infections and will likely impact the development of new therapeutics that target microglia.